Intracellular Transport Routes for MHC I and Their Relevance for Antigen Cross-Presentation - Adiko, Aimé Cézaire; Babdor, Joel; Gutiérrez-Martínez, Enric; Guermonprez, Pierre; Saveanu, Loredana (Frontiers in Immunology, 2015)
Cross-presentation, in which exogenous antigens are presented via MHC I complexes, is involved both in the generation of anti-infectious and anti-tumoral cytotoxic CD8+ T cells and in the maintenance of immune tolerance. While cross-presentation was described almost four decades ago and while it is now established that some dendritic cell subsets are better than others in processing and cross-presenting internalized antigens, the involved molecular mechanisms remain only partially understood. Some of the least explored molecular mechanisms in cross-presentation concern the origin of cross-presenting MHC I molecules and the cellular compartments where antigenic peptide loading occurs. This review focuses on MHC I molecules and their intracellular trafficking. We discuss the source of cross-presenting MHC I in dendritic cells as well as the role of the endocytic pathway in their recycling from the cell surface. Next, we describe the importance of the TAP peptide transporter for delivering peptides to MHC I during cross-presentation. Finally, we highlight the impact of innate immunity mechanisms on specific antigen cross-presentation mechanisms in which TLR activation modulates MHC I trafficking and TAP localization.